The effectiveness of using a set of static exercises in the process of training figure skaters specializing in singles and pairs skating at the educational and training stage and the stage of improving sportsmanship - Zhgun, E.V.; Smirnova, A.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to develop and experimentally test the effectiveness of using a set of static exercises in order to increase the level of physical fitness of figure skaters at the educational and training stage and the stage of improving sportsmanship in single and pair skating using static exercises.